Parasitism and fluctuating asymmetry in Liolaemus darwinii (Squamata: Liolaemidae) from Argentina - Castillo, Gabriel Natalio (2024)
A comparative analysis and investigation of the relationship between the parasite Physaloptera retusa (Physalopteridae) and the fluctuating asymmetry (FA) of the lizard Liolaemus darwinii from Argentina was carried out. In this study, the effect produced by the presence of P. retusa on the symmetry of the heads of lizards has been investigated. Thirty specimens (12 parasitised and 18 non-parasitised) from a population of L. darwinii were examined. The results obtained showed statistical differences in fluctuating asymmetry between parasitised and non-parasitised specimens; the parasitised L. darwinii specimens presented greater head asymmetry compared to the non-parasitised ones, confirming the initial hypothesis. The present study allowed us to consider the analysis of fluctuating asymmetry as a tool that, together with parasites, can be considered and be useful in studies related to reptile populations and in conservation biology.